Peran Sertifikasi Halal Food Pada Bisnis Sesuai Syariat Islam - Annisa Uljannah; Chuzaimah Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The purpose of this paper is to know the halal of a product that will be a mandatory requirement for every consumer, especially muslim consumers. With the written halal label certification on a product will make an effective input for consumers to choose a halal product easily and is an obligation that must be fulfilled by manufacturers in doing business as well as protecting consumers. This Paper uses a descriptive qualitative method by reviewing the relevant literature in Indonesia.